Exploring the impacts of school reforms on underrepresented urban students’ college persistence - Yavuz, Olcay (Educational Research and Evaluation, 2016)
This longitudinal quantitative study investigates how participation in the Comprehensive College Readiness Access and Success Program (CCRASP) affects underrepresented urban students’ college persistence. Results revealed that CCRASP participation was associated with higher percentages of students enrolling in both 2- and 4-year colleges as sophomore students. As school leaders and policy makers seek to make all urban students college and career ready, these findings further solidify current urgencies to re-visit K–12 student academic and counselling services. It also provides school leaders and educators with practical information and reform ideas to improve underprivileged students’ persistence and success. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Research-supported school reforms; at-risk students; college persistence; dept.edl; programme evaluation